FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KABUPATEN GROBOGAN - Nurhana - -; Maryono - - (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to determine the factors that influence taxpayer compliance in paying motor vehicle taxes in Grobogan Regency. The factors tasted in this study are knowledge of taxation, tax sanctions, quality of tax service, and the application of E-SAMSAT. Sampling a number of 101 respondents using accidental sampling method. Data collection was carried out by distributing questionnaires directly and through the online to taxpayers according to the accidental sampling criteria, then analyzed using multiple linear regression analysis test. The result of this research analysis indicate that tax knowledge and tax sanctions have a positive effect on motor venicle taxpayer compliance. The variable quality of tax service and application of E-SAMSAT shows that these factors have no effect on motor venicle taxpayer compliance.Keywords: Tax Knowledge, Tax Sanctions, Quality of Tax Services, and E-SAMSAT